Evaluation Methods of Entrepreneurship Education and Acquisition of Entrepreneurial Skills among Hospitality Students - Shirandula, Duncan (Journal of Technical Education and Training, 2021)
Entrepreneurship education (EE) has been identified as the requisite driver for improving Kenya’s tourism economy. Consequently, the sector has emphasized entrepreneurship education to bolster entrepreneurial skills alongside core technical skills among hospitality graduates in Technical Training Institutes (TTIs), to boost their employability or capacity to start their ventures. However, concerns remain regarding the inadequacy of soft skills among youth despite having the necessary technical training. This study examined the relationship between evaluation methods of EE and acquisition of entrepreneurial skills among students in 5 selected public TTIs in Kenya. The study adopted an explanatory research design. The target population comprised 199 students pursuing a diploma course in Food and Beverage Production, Service and Sales Management from the selected TTIs. A sample of 132 students was selected using stratified and simple random sampling methods. Questionnaires were administered to students. The simple regression method was employed to analyze the data. The findings provide evidence of a positive relationship between evaluation methods of EE and acquisition of entrepreneurial skills (B=3.366, p=.000). It was evident that the use of end-term sit-in exams; participation in class by answering questions and, sit-in tests were the predominant methods adopted. Such methods were found to be theoretical-based and examination-oriented and thus inadequate to evaluate a high level of entrepreneurial skills. Therefore, recommendations are made to TTIs to adopt practical-oriented methods and establish self-regulatory practices to monitor quality compliance to the EE syllabus.